Stevens-Johnson syndrome with a recall-like reaction within a donor graft site. Issue 1 (2nd January 2021) - Najmi, Maleka; Sharp, Leigha; Tarbox, Michelle; Stetson, Cloyce
Abstract: We describe a 69-year-old white man with a recent history of a left forearm sarcoma resection treated with a split-thickness skin graft and radiotherapy who presented with cellulitis of the left forearm, for which a 2-week course of trimethoprim-sulfamethoxazole was prescribed. Ten days into treatment, he presented with flu-like symptoms and a rash. He was eventually diagnosed with Stevens-Johnson syndrome accentuated on the donor split-thickness skin graft on the left thigh region mimicking a recall reaction. There are no other reported cases of Stevens-Johnson syndrome localized within donor graft sites; therefore, this case may represent a novel form of recall reaction.